AB0177 Patient-Reported Outcome of Upper Extremity Surgery for Rheumatoid Arthritis. (15th July 2016) - Kaneda, D.; Ohashi, H.; Takeshita, A.; Horita, M.; Machida, T.; Nakahara, R.; Nasu, Y.; Hashizume, K.; Nishida, K.; Ozaki, T.
Abstract : Background: The goal of treat to target (T2T) is the clinical remission in patients with early disease, but it is difficult to achieve the functional remission. Although patient's subjective evaluation is important for the assessment of postoperative functions of rheumatoid arthritis (RA) patients, there are few reports examined the patients-reported functions after upper extremity surgery for RA. Objectives: Between 2011 and 2014, 158 RA patients underwent the surgical treatment on upper extremities, and all patients were available for detailed clinical review over a 1-year follow-up period. There were 144 females and 14 males with a mean age at surgery of 59.7 (range, 18–85) years. The average disease duration at the surgery was 19.6 (range, 1–59) years. Methods: The clinical outcome of the surgery was assessed by the disease activity (DAS28-CRP), Health Assessment Questionnaire Disability Index (HAQ-DI), Disability of Arm Shoulder and Hand (DASH), Hand20 questionnaire (Hand20). The patients were divided by surgical site into 3 groups (elbow, wrist and finger groups) and by the use of biological disease-modifying anti-rheumatic drugs (bDMARDs) into 2 groups (bDMARDs and non-bDMARDs groups) to compare and evaluate the outcomes. Results: The mean of preoperative/postoperative DAS28-CRP, HAQ-DI, DASH and Hand20 were 2.9/2.3, 0.88/0.94, 46.4/39.1 and 59.1/47.6, respectively. All outcomes except for HAQ-DI significantly improved after the surgery. All outcomes improved significantly in the elbow group, but could not reach significant improvement in the finger group. We further examined the postoperative change in each items of DASH and Hand20, and found the significant improvements in items about pain and weakness in elbow group, pain and rotation of forearm in wrist group, and delicate movement and cosmetic factor in finger group. Postoperative DASH and Hand20 scores were tend to improve in the both bDMARDs and non-bDMARDs group. Conclusions: Our results confirmed the surgery on upper extremity of RA improved the patient's reported function, as well as the disease activity. There were surgical site-specific pattern of improvement of DASH and Hand20, such as that gross movement and pain significantly improved in larger joints, and dexterity movement and cosmetic factor in smaller joints. Postoperative upper extremity function was tend to improve, but more significantly in non-bDMARDs group, probably because the patients might had relatively better baseline function in the bDMARDs group. Understanding of site-specific patterns of improvement after surgery might be useful to achieve the functional remission, and may contribute to decision making of surgical indication, priority of surgical site on upper extremity, and prospection of surgical outcome. References: Moromoto H, et al. Reliability of the Hand20 questionnaire: comparison with the 36-Item Short-Form Health Survey. Hand Surg. 2014;19(1):1–6 Hudak PL, et al. Development of an upper extremity outcome measure: the DASH (disabilities of the arm, shoulder and hand) [corrected]. The Upper Extremity Collaborative Group (UECG). Am J Ind Med. 1996 Jun;29(6):602–8. Disclosure of Interest: None declared